Evaluation of perceived indoor environmental quality of five-star hotels in China: An application of online review analysis. (January 2017) - Qi, Meiwei; Li, Xiaofeng; Zhu, Enwei; Shi, Yuchen
Abstract: Hotel guest perception of Indoor Environmental Quality (IEQ) is significant for both hotel management and IEQ research. This paper used a novel text-mining methodology to analyse guest perception of IEQ through online hotel reviews. More than 160, 000 reviews from 70 five-star hotels were collected from Ctrip.com, the largest travel website in mainland China. Next, a list of IEQ keywords were programmed to extract specific IEQ problems from these reviews. Finally, a complaint indicator was proposed to evaluate customer IEQ dissatisfaction. The results showed an average of four complaints (about indoor environment) per one hundred online reviews. Air conditioning, noise, and humidity were the top three factors influencing guest IEQ satisfaction, representing 39, 23, and 19%, respectively. This paper also revealed that a higher IEQ complaint rate resulted in a lower online rating; as such, IEQ rate indirectly affected the business performance of the hotel. This research also considered the baseline energy consumption of 5-star hotels; if the annual energy consumption was lower than 150 kWh/m 2 a, then indoor environmental performance was significantly compromised. However, if energy consumption was higher than 150 kWh/m 2 a, then there was no obvious negative correlation between the IEQ complaint rate and energy consumption. Highlights: A new method to analyse perceived IEQ from online hotel reviews was proposed. The average online IEQ complaint rate of 5-star hotels in China was 4%. It provided a baseline in energy consumption for 5-star hotels in China on the basis of online IEQ complaint rates.